The Effect of Effectiveness Ratio, Efficiency Ratio, Harmony Ratio and Financial Growth Ratio Region Towards Financial Performance Medan City Government and Tebing Tinggi City - Ismayani; Nasution, M. Irsan; Maisyarah, Renny (PT FORMOSA CENDEKIA GLOBAL, 2024)
The Regional Revenue and Expenditure Budget (APBD) is a key policy tool used by local governments to support operational activities and regional development. The ability to manage the APBD reflects the local government's capacity to meet the financing needs. This study aims to analyze the partial and simultaneous effects of regional financial performance, effectiveness ratio, efficiency ratio, harmony ratio, and growth ratio on the level of regional independence in the City Government of Medan and Tebing Tinggi. The research adopts a descriptive quantitative approach with testing through multiple linear regression analysis, utilizing secondary data obtained from the official website www.djpk.kemenkeu.go.id. The findings show that, in a partial analysis, the effectiveness ratio (X1), efficiency ratio (X2), harmony ratio (X3), and growth ratio (X4) have a significant impact on the regional financial performance, with each having a significance value of 0.00 (< 0.05). However, when analyzed simultaneously, these four variables do not significantly influence the regional independence ratio. This study, conducted over the period from 2019 to 2023 with a 95.5% confidence level, is expected to serve as a reference for local governments to enhance the effectiveness and efficiency of financial management in the future